The Translation Techniques Of Impoliteness Markers In The Film Adaptation Of Jane Austen's "Pride And Prejudice" - Suryani , Ani; Nababan , Nababan; Nugroho , Miftah (International Journal of Educational Research & Social Sciences, 2024)
This research aims to analyze the translation techniques used by translators to translate impoliteness markers in the film adaptation of Jane Austen’s "Pride and Prejudice". The approach used in this research was translation approach with descriptive qualitative research type because it was oriented towards translation products. This research data was taken from dialogue between characters in the film in which contains markers of impoliteness. Then, the data source in this research was taken from the film adaptation of Jane Austen’s "Pride and Prejudice". The translation technique used to analyze in this research are translation techniques compiled by Molina and Albir (2002). The results of this research showed that there were 12 translation techniques used by translator to translate impoliteness markers. These techniques are establishing equivalent, variation, implication, explication, discursive creation, paraphrase, borrowing, compensation, modulation, reduction, generalization, and transposition.